Effect of Integrated Nutrient Management on Mango (Mangifera indica L.) cv. Himsagar - H D Talang (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2017)
A field experiment was carried out for two years (2012-13 and 2013-14) to study the effect of integrated nutrient management comprising of biofertilizers (Azospirillum, Azotobacter, Trichoderma and Pseudomonas) conjointly with chemical fertilizers and organic manures on growth, yield and quality as well as soil chemical properties of mango cv. Himsagar at Bidhan Chandra Krishi Viswavidyalaya, Regional Research Station, Gayeshpur. Result revealed that treatment with half (1000:500:1000 g NPK/tree) + 50 kg FYM + Azospirillium (250 g) + 100 g potassium mobiliser (T6) recorded maximum plant height (5.79 m), girth (64.91 cm) and plant spread in east-west (5.63 m) and north-south direction (5.46 m) than the other treatments. The treatment T8 consisting of half (1000:500:1000 g NPK/tree) + 50 kg FYM + 5 kg vermicompost + 100 g potassium mobiliser recorded maximum number of fruits (230.31 / tree), fruit weight (261.48 g), yield (60.22 kg /tree) and also have a significant improvement in terms of TSS (19.66 0Brix), total sugars (16.48 %), ascorbic acid (33.56 mg/100 g pulp), â-carotene (6935 μg/100g pulp) and shelf life (9 days) at room temperature as compared to other treatments, concomitant with higher values of soil (N-198.22 kg/ha, P-58.44 kg/ha and K-326.93 kg/ha) and leaf nutrient (N- 1.77 %, P-0.67 % and K-1.08 %) contents.